Does storage technology affect adoption of improved maize varieties in Africa? Insights from Malawi's input subsidy program. (January 2015) - Ricker-Gilbert, Jacob; Jones, Michael
Highlights: We use panel data of smallholder farm households in Malawi. We examine effects of previous-season storage chemical use on improved maize adoption. We find increases of 6.6 – 9.0% in average probability of planting improved seed. We also find increased area and crop share dedicated to improved maize varieties. Further, > 50% crowding out of commercial storage chemicals occurs with subsidies. Abstract: To date there is limited knowledge of how having access to post-harvest storage technology affects a smallholder African farmer's decision to adopt higher-yielding improved maize varieties. This is a key issue because higher yielding varieties are known to be more susceptible to storage pests than lower-yielding traditional varieties. We address this question using panel data from Malawi, and incorporating panel estimation techniques to deal with unobserved heterogeneity. Our results indicate that acquiring chemical storage protectants after the previous harvest is associated with a statistically significant and modest positive impact on the probability of adopting improved maize, total area planted to improved maize varieties, and share of area planted to improved maize varieties in the next planting season. We also find that the storage chemical subsidy is associated with significant crowding out of commercial storage chemical purchases, as farmers who acquire subsidized chemicals are more than 50 percentage points less likely to purchase commercial chemicals on average. These findings have implications for maize adoption and input subsidy policies, and they indicate that researchers, extension staff, and policy makers should consider post-harvest issue when promoting adoption of improved varieties.